(untitled) (Plant Tissue Culture and Biotechnology, 2018)
A protocol for in vitro multiplication and callus proliferation of jojoba was developed. Nodal segments were cultured on MS supplemented with 1 mg/l BA. For multiplication, combination of 1.5 mg/l BA + 1 mg/l IAA resulted in greater number of shootlet. While, 1 mg/l BA + NAA enhanced the height of shootlet and number of nodes. Also, the effect of adenine sulfate and TDZ on shootlets multiplication was examined. The maximum number of shootlets emergence was obtained with medium contained 30 mg/l adenine sulfate. Likewise, the used levels of TDZ specially 2 mg/l enhanced shootlets proliferation as well as length of shootlet and number of nodes. Callus induction using combinations of NAA or picloram with BA or Kn was evaluated. The maximum callus frequency was observed with 5 mg/l BA + 1 mg/l picloram followed by 5 mg/l BA + 2 mg/l picloram containing medium. It was found that fresh mass and growth value increased gradually till the third subculture. Plant Tissue Cult. & Biotech. 28(2): 201-214, 2018 (December)